Communications Methods Used by Agricultural Extension Agents - Dasse' Bouare; Blannie E. Bowen (Journal of Applied Communications, 1990)
Ohio agricultural Extension agents were studied to determine which communications methods they used to deliver instruction in five subject matter areas. Methods the agents used were the ones they perceived to be most appropriate for use with farmers. Office calls, telephone calls, bulletins, and newsletters were the methods used most often by OCES agents. Methods used least were the mass media (radio, television, and magazines) and teleconferencing. Two major conclusions reached in the study were: 1) the subject matter that the agents delivered was not what they perceived to be most important, and 2) the methods that the agents used most often were the ones that they deemed most lrnportant.